MEASURES FOR PROTECTING VISUAL AND AUDITORY ANALYZERS IN INDIVIDUALS ENGAGED IN MENTAL LABOR (Symposium on Natural and Applied Sciences, 2026)
In recent years, the widespread implementation of digital technologies has led to increased visual load and acoustic exposure, resulting in decreased visual acuity, the development of “digital eye syndrome,” and functional impairments of the auditory analyzer. According to the World Health Organization, at least 2.2 billion people worldwide experience vision-related problems, a significant proportion of which are preventable. At the same time, more than 1 billion young individuals are exposed to hazardous levels of noise.